Sharing fake news about health in the cross-platform messaging app WhatsApp during the COVID-19 pandemic: A pilot study - Pinheiro, David Araújo; de Araújo, Mariana Gomes Leitão; de Souza, Keilla Barbosa; Campos, Beatriz de Sousa; de Oliveira, Evanete Maria; Melquides Lima, Rosa Stephanny; Ferreira, Gabriella Alves; de Freitas, Aila Caterine Almeida; Toledo, Caroline Barbosa; de Souza, Gabriela Brito; Olivera, Thais Ranielle Souza de; Barbosa, Daniel Fernandes (International Journal of Scientific Research and Management (IJSRM), 2020)
In the current scenario of the COVID-19 pandemic, a lot of false information has spread through social networks. This study aimed to characterize the types of fake news in health and the factors that influence its sharing. This is a descriptive cross-sectional observational study conducted by health scholars who analyzed the messages received in the WhatsApp network and the sociodemographic characteristics of sharers in the year 2020. Results: The level of education influences the spread of false news, and family members have a higher frequency of sharing these news. As for the type of content of fake news, the fabricated content and false context stood out as the most shared ones. The characteristic of the group of researchers may have influenced the receivement of a smaller amount of fake news, since they are able to recognize and refute